2020
DOI: 10.1007/s11869-020-00892-w
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution improvement and mortality rate during COVID-19 pandemic in India: global intersectional study

Abstract: This research was carried out using the open-source database system along with the continuous air quality monitoring station results from global data sets during the COVID-19 pandemic lockdown in India and the global. Our purpose of this research is to study the improvement of air quality and human mortality rates in countries worldwide during the COVID-19 pandemic lockdown. Worldwide air quality data were collected from > 12,000 continuous air quality monitoring stations on six continents covering 1000 major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 32 publications
1
43
0
1
Order By: Relevance
“…Isaifan (2020) recorded a substantial decrease in NO 2 and carbon emissions (30% and 25%, respectively) in China, which correlated to industrial lockdowns. Karuppasamy et al (2020) documented a 55% contraction in NO 2 in India during the lockdown. A recent analysis in the Middle East has also shown a decrease in the number of air pollutants in Morocco of 75%, 49%, and 96% for PM 10 , SO 2 , and NO 2 , respectively ( Otmani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isaifan (2020) recorded a substantial decrease in NO 2 and carbon emissions (30% and 25%, respectively) in China, which correlated to industrial lockdowns. Karuppasamy et al (2020) documented a 55% contraction in NO 2 in India during the lockdown. A recent analysis in the Middle East has also shown a decrease in the number of air pollutants in Morocco of 75%, 49%, and 96% for PM 10 , SO 2 , and NO 2 , respectively ( Otmani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isaifan (2020) reported a significant drop in N 2 O and carbon emissions (i.e., 30 and 25%, respectively) in China, due to industrial lockdown. Karuppasamy et al (2020) reported a 55% reduction in NO 2 in India during the lockdown period. Additionally, it is hypothesized that different air pollutants may have a significant relationship with COVID-19 infections, although they are not fully examined, and there remains uncertainty .…”
Section: Introductionmentioning
confidence: 99%
“…The predicted values would represent the mortality if there were no COVID-19 lockdown scenario. However, due to episodic changes in PM 2.5 concentrations in India during COVID-19 lockdown (Karuppasamy et al 2020;Singh and Chauhan 2020), a reduction in 2020 mortality values is expected. This potential reduction in mortality is calculated using the developed concentration-response function and obtained changes in PM 2.5 concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, several governments have been implementing nationwide lockdowns, restricting most nonessential activities to limit the virus's spread. closure While the cost of enforcing these restrictions is enormous, numerous studies reported a silver lining to COVID-19 lockdowns in terms of reduced ambient air pollution due to decreased anthropogenic activities (Chen et al 2020;Karuppasamy et al 2020;Singh and Chauhan 2020).…”
Section: Introductionmentioning
confidence: 99%